2011
DOI: 10.1007/s00420-011-0716-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor function in ship welders after cessation of manganese exposure

Abstract: In the present study of welders with previous welding fume exposure, former welders and referents performed similarly in most of the neurobehavioral tests. Previous adverse effects on the neuromotor system might have ceased, and decreased neuromotor function due to normal aging processes in both groups might have disguised any slight effect of previous Mn exposure. The poorer performance in the grooved pegboard test among welders may indicate an adverse effect on motor function of long-term exposure to Mn, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Different performance alterations being related to different exposure conditions might be concluded from epidemiological data on pegboard tests that could not be analyzed herein. Cowan et al (2009b) and Chang et al (2009) found in active welders, Ellingsen et al (2008) and Wastensson et al (2012) in retired welders significantly lower performances in a pegboard test. Mergler et al (1994), Bast-Pettersen et al (2004), and Sjögren et al (1996) did not find significant differences.…”
Section: Discussionmentioning
confidence: 87%
“…Different performance alterations being related to different exposure conditions might be concluded from epidemiological data on pegboard tests that could not be analyzed herein. Cowan et al (2009b) and Chang et al (2009) found in active welders, Ellingsen et al (2008) and Wastensson et al (2012) in retired welders significantly lower performances in a pegboard test. Mergler et al (1994), Bast-Pettersen et al (2004), and Sjögren et al (1996) did not find significant differences.…”
Section: Discussionmentioning
confidence: 87%
“…Of the 66, 7 were also identified in the “NCTB” search (i.e., Table 1 above) and excluded from this assessment. Thus 59 articles were reviewed to determine if they used any NCTB tests and if they used at least 5 of the tests indicating they had substantially used the “core” set of NCTB tests (Dolbec et al 2000; Letz et al 2000; Lucchini et al 2000; Schwartz et al 2000; Steenland et al 2000; Triebig et al 2000; Deschamps et al 2001; Ellingsen et al 2001; Frumkin et al 2001; Schwartz et al 2001; Hwang et al 2002; Polizzi et al 2002; Wesseling et al 2002; Bouchard et al 2003; Carta et al 2003; Gong et al 2003; Kamel et al 2003; Lucchini et al 2003; Mascagni et al 2003; Urban et al 2003; Chuang et al 2004; Kilburn 2004; Kilburn 2004; Kunert et al 2004; Bast-Pettersen and Ellingsen 2005; Bast-Pettersen et al 2005; Chen et al 2005; Rohlman et al 2005; Roldan-Tapia et al 2005; Vouriot et al 2005; Dorsey et al 2006; Echeverria et al 2006; Rothlein et al 2006; Schofield et al 2006; Winker et al 2006; Bleecker et al 2007; Blond et al 2007; Bouchard et al 2007; Eckerman et al 2007; Iwata et al 2007; Keski-Santti et al 2007; Lee et al 2007; Rohlman et al 2007; Shin et al 2007; Abdel Rasoul et al 2008; Bouchard et al 2008; Ellingsen et al 2008; Scapellato et al 2008; Wastensson et al 2008; Chang et al 2009; Cowan et al 2009; Hilt et al 2009; Kaukiainen et al 2009; Kim et al 2011; Lucchini et al 2012; Lucchini et al 2012; Rentschler et al 2012; Starks et al 2012; Wastensson et al 2012). From the sample of 59, 37 studies (63%) used at least 1 NCTB test, and 5 (8.5%) used 5 or more NCTB tests.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Thus, some studies have applied the tremor test with a longer recording time of 16.4 s [22,[27][28][29] or even 24.6 s [24]. However, in most cases the test was administered only once.…”
Section: Recording Timementioning
confidence: 99%
“…The correlation (Spearman, r s ) between Tremor Intensity as measured by the CATSYS Tremor Pen and the Static Steadiness Test was highest for the 16 second recording (Figure 3), both for number of contacts where r s= 0.56 (range: 0.47-0.50 for the other recording times) and duration of contacts where r s= 0.65 effects associated with this measure [13,18,[20][21][22]. Bowler et al [16] reported impaired results in HI among manganese-exposed welders, but the values indicate that the results were for a measure other than the HI.…”
Section: Comparison Between Catsys Tremor Pen and Static Steadiness Testmentioning
confidence: 99%
See 1 more Smart Citation